Myofascial Pelvic Pain: An Overlooked and Treatable Cause of Chronic Pelvic Pain. (31st March 2021) - Ross, Vanessa; Detterman, Carly; Hallisey, Anastasia
Abstract: Myofascial pelvic pain is a common, nonarticular musculoskeletal disorder characterized by the presence of myofascial trigger points in the lower abdominal wall and/or pelvic floor muscles. Myofascial pelvic pain is involved in an estimated 22% to 94% of cases of chronic pelvic pain, which is one of the most common gynecologic conditions in the United States. Myofascial pelvic pain may exist independently or in conjunction with disorders such as vaginismus, dysmenorrhea, and endometriosis and is frequently a causative factor in sexual pain or dyspareunia. This article reviews the pathophysiology, assessment, and treatment options for myofascial pelvic pain, with a particular focus on trigger point injections. Increased recognition and treatment of this commonly overlooked diagnosis has the potential to improve care and outcomes for many patients suffering from chronic pelvic pain.